Study of Fabrication on Sponge Aluminum by Investment Casting. Issue 1 (13th June 2022) - Youchao, Wang; Pengfei, Chen; Guofa, Mi; Yuan, Liu; Tan, Wan; Weidong, Liu
Abstract: Sponge aluminum ranged from 10 to 40 PPI was fabricated by investment casting combined with vacuum infiltration, the effects of infiltration temperature, pressure and size of infiltration channel on the infiltration length were systematically studied theoretically and experimentally. The results show that the infiltration temperature difference has little effect on the infiltration length of aluminum foam with the same pore grades. With the increase of infiltration pressure and the decrease of infiltration channel size, the infiltration length increases. By increasing the infiltration pressure to 2 MPa and the infiltration temperature to 700 °C, aluminum sponge with high pore grades can be prepared. Under the same infiltration channel, the porosity of aluminum foam is the same. At this point, the applied infiltration pressure increases and the infiltration length increases. In order to ensure that the infiltration length of sponge aluminum with large pore grades is the same as that of sponge aluminum with small pore grades, the infiltration pressure should be increased. When the size of the infiltration channel, namely the pore grades, remains unchanged, and the infiltration temperature of the metal fluid is increased, the infiltration length will increase. However, it is necessary to consider the gypsum temperature. If the infiltration temperature is too high, the gypsum temperature will be too high, resulting in cracks in the gypsum type and defects in the sponge aluminum. When preparing sponge aluminum with high pore grades, it is necessary to raise the infiltration temperature of the metal liquid in order to obtain the same infiltration length.